Meningkatnya Quality of Life (QoL) dengan Intervensi Senam Kaki dan Aromatherapy Lavender Pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Rambipuji - Hella Meldy Tursina; Yuniasih Purwaningrum; Eka Anggita Febrianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2019)
Quality of life is a term that shows the physical, social and emotional health of a person and the ability to carry out daily tasks. The reality is diabetes can affect a person's life, one of which is the presence of gangrene wounds which worsen the quality of life. Complementary and Alternative Medicine (CAM) is used as a supportive therapy to improve health. Foot exercise and Aromatherapy lavender is relaxation that improves physical and mental health. The research design used was Quasi Experiment design with One Group Pre and post design approach, the sampling technique used was Simple Random Sampling with 16 respondents. Respondents in this study were diabetes mellitus patients in Rambipuji Health Center. This research was conducted by giving a WHOQOL-BREF questionnaire to determine differences in quality of life with foot gymnastic interventions and Lavender Aromatherapy. The results of this study indicate that most of the quality of life of respondents before being given an intervention is at medium quality of life which is 13 respondents (81.3%) and after being given an intervention are at a good quality of life that is 14 respondents (87.5%). Based on the results of the statistical analysis, the results show that a p-value of 0,000 means that there is an influence on the QoL of patients with diabetes mellitus before and after foot gymnastics and aromatherapy lavender therapy at the Rembipuji Healt Center in 2019. Foot exercises and the aroma of lavender therapy can be done as a supportive therapy to improve the quality of life of patients with type 2 diabetes mellitus. The results of this study can be used as one method in improving the quality of life patients with diabetes mellitus by doing foot exercises regularly 3 times a week and lavender aromatherapy every night before going to bed. It can maintain blood sugar levels in a normal state and quality of life stable or improved.